The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1039/c1pp05224a
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in UV-induced inflammation and immunosuppression in mice reveal male unresponsiveness to UVA radiation

Abstract: Immunosuppression attributed mainly to the UVB (290-320 nm) waveband is a prerequisite for skin cancer development in mice and humans. The contribution of UVA (320-400 nm) is controversial, but in mice UVA irradiation has been found to antagonise immunosuppression by UVB. In other studies of photoimmune regulation, protection mediated via oestrogen receptor-β signalling was identified as a normal endogenous defence in mice, and was shown to depend on UVA irradiation. A gender bias in photoimmune responsiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 35 publications
5
24
0
Order By: Relevance
“…Some studies suggest differences between male and female tanning behaviour, such as sun protection use, amount of time spent in the sun, likeliness to use sunbeds and varying risks for sunburn and melanoma [34,35]. According to previously published studies, gender-imbalanced morbidity and mortality rates may root in different cellular and molecular properties of skin cancer [36][37][38]. In our survey, we also found some significant differences in gender-related attitudes and motives regarding having or not having a tanned skin.…”
Section: Resultsmentioning
confidence: 96%
“…Some studies suggest differences between male and female tanning behaviour, such as sun protection use, amount of time spent in the sun, likeliness to use sunbeds and varying risks for sunburn and melanoma [34,35]. According to previously published studies, gender-imbalanced morbidity and mortality rates may root in different cellular and molecular properties of skin cancer [36][37][38]. In our survey, we also found some significant differences in gender-related attitudes and motives regarding having or not having a tanned skin.…”
Section: Resultsmentioning
confidence: 96%
“…That is, males, naturally deficient in estrogen and ER signaling, do not exhibit reductions in contact hypersensitivity induced by solar stimulated radiation, suggesting that females are more protected than males to NMSC. However, the same study demonstrated that male mice exposed to both UVA and UVB had less inflammatory edema compared to females due to their naturally thicker skin (presumably due to increasing thickness of the dermis and subdermal muscle layer) and decreases in levels of proinflammatory IL‐6 specific to males 40. In another study, Sullivan et al 41.…”
Section: Discussionmentioning
confidence: 92%
“…As noted above, in this model, and in human keratinocytes, 1,25D reduces interleukin-6 expression [25,63] and this may be an action of 20OHD as well, though this remains to be tested. There is evidence that metallothionein knockout mice are more susceptible to UV-induced immunosuppression, compared to the wild type [69]. As metallothionein mRNA expression is induced by 1,25D [70], this mechanism might also contribute to the reduction in photoimmune suppression by 1,25D and possibly 20OHD, although whether 20OHD induces metallothionein is unknown at this time..…”
Section: Discussionmentioning
confidence: 95%